Residual strength of blast damaged reinforced concrete columns - Nair, Anand (2010)
Columns are key load-bearing elements that hold up framed structures. Exterior columns are probably the most vulnerable structural components to attacks from rebel forces. Their failure could possibly trigger a progressive collapse of an entire structure. Current knowledge of blast-damaged axial load carrying capacity of reinforced concrete columns is rather limited. A better understanding of column behaviour when subjected to blast loadings would be able to provide essential information on its damage assessment enabling the forecasting of a progressive collapse of a structure. An explosion creates a rapid release of a massive amount of energy. This energy usually takes the form of light, heat, sound and a shock wave. This shock wave is made up of condensed air pressures and travels outwards at supersonic velocities. When this wave encounters a building structure, it could cause it extreme damage if not designed to resist blast effects. Numerical and experimental studies were carried out to determine the response and behaviour of columns when subjected to blast loadings. The numerical approach utilized computer simulation of blast effects on a specimen modeled to represent actual column specimens. The deflections obtained from the numerical analysis were used to recreate the damaged profile attained by the model on actual column specimens in a laboratory environment. Hydraulically powered actuators were used to push out a column to the blast damaged profile obtained from the computer-generated model. The effects of parameters such as pre-axial loading and transverse reinforcement ratio are investigated in this study.